A smart off–on copper sulfide photoacoustic imaging agent based on amorphous–crystalline transition for cancer imaging. Issue 78 (17th September 2018) - Feng, Qunfeng; Xu, Yanjun; Hu, Bing; An, Lu; Lin, Jiaomin; Tian, Qiwei; Yang, Shiping
Abstract : By exploiting the amorphous–crystalline transition of CuS, which results in greatly increased absorption throughout the entire near-infrared region, a novel smart off–on CuS photoacoustic imaging agent with good photostability and low cost is developed. Abstract : By exploiting the amorphous–crystalline transition of CuS, which results in greatly increased absorption throughout the entire near-infrared region, a novel smart off–on CuS photoacoustic imaging agent with good photostability and low cost is developed. More importantly, the photoacoustic imaging ability of CuS can be effectively activated by body temperature for in vivo cancer imaging.